Role of Inventory Management on Competitive Advantage of Small and Medium Companies in Thailand - et. al., Pornthep Kaewchur, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were to study the inventory management factors affecting the competitive advantage and confirm the inventory management factors affecting the competitive advantage. This research was a mixed methods research. First, the quantitative data was collected from the sample of 280 small and medium companies in Thailand. This research focused on 14 observable variables. Then, the qualitative data was collected from nine key informants who were the experts in the inventory management field. The results indicated that the structural equation model was consistent and harmonious with the empirical data with the model consistency indices as follows: 2= 106.32, df = 69, 2/ df = 1.54, CFI = 0.99, GFI = 0.95, SRMR = 0.042, RMSEA = 0.044. Furthermore, the inventory control systems had the greatest influence on the competitive advantage, followed by inventory control practices, and information technology, respectively.